2000
DOI: 10.1083/jcb.150.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Slows Axonal Transport of Neurofilaments in Transfected Neurons

Abstract: Neurofilaments are transported through axons by slow axonal transport. Abnormal accumulations of neurofilaments are seen in several neurodegenerative diseases, and this suggests that neurofilament transport is defective. Excitotoxic mechanisms involving glutamate are believed to be part of the pathogenic process in some neurodegenerative diseases, but there is currently little evidence to link glutamate with neurofilament transport. We have used a novel technique involving transfection of the green fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
132
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 91 publications
(148 reference statements)
12
132
0
2
Order By: Relevance
“…In patients with ALS, microgliosis occurs specifically with motor neuron injury in the motor cortex, along the corticospinal tract, and in the ventral horn of the spinal cord [24,53,[69][70][71][72] radioligands that bind microglia, has been used to image microglial activation corresponding with the location motor neuron injury in patients with ALS [72,73]. This radiographic evidence in humans correlates the with evidence in the G93A mSOD1 transgenic mouse, which demonstrates microglial activation even before motor neuron cell death [74,75].…”
Section: Microgliamentioning
confidence: 83%
See 4 more Smart Citations
“…In patients with ALS, microgliosis occurs specifically with motor neuron injury in the motor cortex, along the corticospinal tract, and in the ventral horn of the spinal cord [24,53,[69][70][71][72] radioligands that bind microglia, has been used to image microglial activation corresponding with the location motor neuron injury in patients with ALS [72,73]. This radiographic evidence in humans correlates the with evidence in the G93A mSOD1 transgenic mouse, which demonstrates microglial activation even before motor neuron cell death [74,75].…”
Section: Microgliamentioning
confidence: 83%
“…Most importantly, many of these immune changes in the animal model have been confirmed in patients with nonhereditary ALS [24,70,99,100,131,132]. Henkel et al [133] demonstrated that in patients with rapidly progressing clinical states, an inverse correlation was seen between Treg numbers in the blood and leukocyte levels of FoxP3, a transcription factor required for Treg suppressive function [134].…”
Section: Neuroinflammation In Patients With Als: Tregsmentioning
confidence: 99%
See 3 more Smart Citations